Food sovereignty and local public policies: the traditional market of Miahuatlan de Porfirio Diaz, Oaxaca - Osorio Alvarado, Florinda; Camacho Vera, Joaquín Hhuitzilihuitl; Durán Férman, Guadalupe Gabriel; López García, Arturo César (Acta Universitaria, 2022)
Traditional markets play an important role in generating food sovereignty, but most of them are not considered in public policies because such policies tend to benefit supermarkets and public markets; and in cases where they are considered, rather than favored, they are controlled. The objective was to analyze the influence of public policies implemented by the municipal government on the traditional market of Miahuatlán de Porfirio Díaz regarding its capacity to contribute to food sovereignty. A qualitative approach was used with a theoretical underpinning based on the concept of food sovereignty, traditional market, and municipal public policies. Semi-structured interviews were applied to vegetable producers, municipal authorities, and producer leaders; as well, non-participant and participant observation were also used. The results show that public policies on the traditional market are policies that try to control this activity.